Analisis Faktor Sosial Ekonomi dan Demografis Terhadap Akses Air Bersih dan Sanitasi Layak di Indonesia - Syabila Tania; Mike Triani (Universitas Negeri Padang, 2025)
This study examines the influence of social and demographic characteristics on the availability of clean water and adequate sanitation facilities for households in Indonesia. The focus of the study includes the analysis of variables such as educational background, age range, gender, employment status of the head of the household, level of expenditure, home ownership status, area of residence and geographical location of residence. Methodologically, this study applies a quantitative approach through logistic regression analysis based on Susenas 2020 data with a sample of 334,229 households. The research findings reveal that factors of higher education, productive age, active employment status, adequate economic capacity, and rural location are positively associated with easy access to clean water and sanitation. On the other hand, households with male heads of households, property owners, and those residing in eastern Indonesia actually face limited access. These results identify disparities that require special handling through affirmative policies, especially for disadvantaged areas. Practically, these findings can be a reference in formulating equitable development programs to support the achievement of the SDGs, especially on the sixth goal on clean water and sanitation.